2020
DOI: 10.3390/cells9061333
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Metabolic Vulnerability in Imatinib-Resistant Gastrointestinal Stromal Tumor

Abstract: Metabolic reprogramming is a hallmark of cancer cells in response to targeted therapy. Decreased glycolytic activity with enhanced mitochondrial respiration secondary to imatinib has been shown in imatinib-sensitive gastrointestional stromal tumors (GIST). However, the role of energy metabolism in imatinib-resistant GIST remains poorly characterized. Here, we investigated the effect of imatinib treatment on glycolysis and oxidative phosphorylation (OXPHOS), as well as the effect of inhibition of these energy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Our study further characterized the bioenergetic profile in imatinib-resistant GIST cells. We found that imatinib-resistant GIST cells can harbor high metabolic status (upregulated high glycolysis and OXPHOS status) and low OXPHOS status, suggesting the heterogeneity of metabolic reprogramming in GIST cells surviving imatinib cytotoxicity [169].…”
Section: Energy Metabolism In Gistmentioning
confidence: 85%
“…Our study further characterized the bioenergetic profile in imatinib-resistant GIST cells. We found that imatinib-resistant GIST cells can harbor high metabolic status (upregulated high glycolysis and OXPHOS status) and low OXPHOS status, suggesting the heterogeneity of metabolic reprogramming in GIST cells surviving imatinib cytotoxicity [169].…”
Section: Energy Metabolism In Gistmentioning
confidence: 85%
“…Our findings indicate that glycolysis inhibition and increased OXPHOS activity could explain, at least partially, the inhibition of metabolic reprogramming by melatonin in HNSCC cells. OXPHOS deficiency also closely correlates with the invasive and metastatic properties of tumor cells [ 38 ]. Our results conclude that melatonin treatment increases TCA intermediates such as acetyl-CoA, citric acid, and succinyl-CoA, as well as NADH, but decreases pyruvate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis is generally used by cancer cells for ATP production rather than mitochondrial respiration, even in the presence of adequate oxygen [ 37 ]. In addition, resistant cells can acquire a glycolytic metabolism to survive cytotoxic stress [ 38 ]. Given that glycolytic marker expression in HNSCC is associated with poor survival rates and resistance to chemo and radiotherapy [ 2 ], we observed that melatonin decreases glycolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism of metabolic reprogramming upon imatinib treatment in GIST remains elusive. We previously demonstrated that imatinib also suppressed mitochondrial biogenesis [ 11 ], suggesting that imatinib does not induce OXPHOS through mitochondrial biogenesis. In the present study, we speculate that imatinib might induce OXPHOS through microRNA regulation in GIST.…”
Section: Introductionmentioning
confidence: 99%